VERIFIKASI METODE MBAS TERHADAP PEMANFAATAN FABA DALAM PENURUNAN KADAR SURFAKTAN ANIONIK LIMBAH CAIR DOMESTIK LAUNDRY DI BALIKPAPAN - Paramita, Adhe; Elma, Muthia; Rahma, Aulia; Suryani, Made Yuri (PROSIDING SEMINAR KIMIA, 2024)
The Flay Ash and Bottom ash (FABA) used are derived from the Balikpapan Power Plant. Chemical activation was carried out using a base treatment with NaOH concentrations of 0 and 6 M mixed with FABA at a ratio of 10 mL solution per 1 gram of ash at a temperature of 160°C and then the mixture was dried under neutral conditions at 100°C for 4 hours. The activated FABA was then applied in the treatment of laundry waste. The verification of anionik surfactant parameters in the laundry wastewater samples was conducted based on the MBAS (Methylene Blue Active Substances) method using a UV-Vis spectrophotometer, were in accordance with the SNI 06-6989.51-2005 standard at a wavelength of 652 nm.The results was indicated by the value R2=0.9981 and the value of r=0.9990, equivalent to 99.9%. The limit of detection (LOD) value was determined to be 0.56082 mg/L, while the smallest measurable concentration limit (LOQ) was 1.86941. The precision level measured by %RSD was 0.08965%, which is less than 2/3 of the maximum Horwitz %CV value of 7.82018%. The test data indicates good precision results. The concentration of anionik surfactant also experienced a significant decrease in the case of Flay Ash 6 M. Keywords: bottom ash, flay ash, laundry, surfactant